The Statute of Limitation in Criminal Law of Republic of Serbia - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
It is an established rule that anyone who commits a crime will be convicted by a competent court on the legal basis. However, in practice, since ancient times, the perpetrators have managed to avoid criminal proceedings or execution of a sentence prescribed by the law. This could happen due to the application of the limitation, the amnesty or the pardon rule. Those institutes are used in public interest, mostly for the political or criminal policy purpose, in order for the ius puniendi right of the state to be annulled. Although there are many similarities between these three institutes in terms of their nature, effect, content and importance, major differences between them could be noticed. The limitation is the extinction of the criminal sanction due to a statutory time lapse. This paper is about the characteristics, the content, the effect and the legal nature of amnesty from the normative, theoretical and practical points of view in the modern criminal law of the Republic of Serbia.